1960
DOI: 10.1002/jsfa.2740110201
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of meats with ionising radiations. III.—Radiation pasteurisation of whole eviscerated chicken carcasses

Abstract: Whole eviscerated chicken carcasses were irradiated with y-radiation from 6oCo, using varying doses up to I Mrad. Changes in quality were assessed by submitting samples to a laboratory panel and to a domestic consumer panel ; and the effect of radiation in prolonging the period required for microbial spoilage under chilled conditions of storage was studied. When the meat was stored a t 1 ' c, a dose of 0.8 Mrad gave a five-fold extension of the time required for putrefactive spoilage, and the flavour changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

1960
1960
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…When cooked the barrier-wrapped samples were still described as 'pink', 'pink inside', 'uneven colour' and 'undercooked' and dissociated from all other samples. In contrast to the results of Coleby et al (1960) with chicken, the pinkness in the raw samples was very acceptable to the panel, and these samples were preferred, but after cooking pinkness was not liked.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…When cooked the barrier-wrapped samples were still described as 'pink', 'pink inside', 'uneven colour' and 'undercooked' and dissociated from all other samples. In contrast to the results of Coleby et al (1960) with chicken, the pinkness in the raw samples was very acceptable to the panel, and these samples were preferred, but after cooking pinkness was not liked.…”
Section: Discussioncontrasting
confidence: 67%
“…This was noted in chicken by Coleby et al (1960) and Rhodes (1965). At storage of 1 day, the irradiated barrier-wrapped samples were more pink than the polythene wrapped; after 21 days the polythene wrapped samples were associated with descriptors such as brown, dull, old, soggy (the same as non-irradiated) whilst barrier-wrapped samples were still intensely pink.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Pink color gives the impression that the product is undercooked, and is occasionally found in freshly cut poultry products after cooking. The causes for pink meat, according to the literature, are as follows: 1) carbon monoxide or nitric oxide generated in gas-fired ovens (Pool, 1956); 2) irradiation pasteurization (Coleby et al, 1960;Mead and Roberts, 1986); 3) nitrates or nitrites in the bird's diet (Froning et al, 1967); 4) different concentrations of muscle myoglobin in meat (Froning et al, 1968a); 5) use of spray-dried albumin as a food additive (Froning et al, 1968b); 6) changes in endpoint cooking temperature and storage (Helmke and Froning, 1971); 7) higher cytochrome levels in muscle as a result of preslaughter stress (Babji et al, 1982); 8) inhalation of gases by birds during transport (Froning, 1983); 9) nitrites in processing plant water supplies or from curing procedures (Brant, 1984); 10) leakage of refrigerant gases in the processing plant (Everson, 1984); 11) replacement of muscle nitrosyl pigments with reduced and denatured hemochromes in meat (Cornforth et al, 1986); 12) microbial conversion of nitrates to nitrites during storage (Ahn and Maurer, 1987); and 13) incomplete denaturation of myoglobin during cooking (Trout, 1989). Schmidt and Trout (1984) and Trout (1989) indicated that when cooked to the same internal temperature, beef, pork, and turkey muscle with pH greater than 6.0 became more red in color than muscle with pH 5.5.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in making wider use of this tool in food technology has been shown by the scientific community, industry, and federal agencies (Institute of Food Technologists, 1983;Engel, 1985). The use of irradiation to increase microbiological shelf-life and ensure the safety of various poultry products has received considerable attention (Coleby et al, 1960;Rhodes, 1965;Mercuri et al, 1967;Idziak and Incze, 1968;Kahan and Howker, 1978). Most of the published research concerned with the nutritional, microbiological, and toxicological aspects of fresh red meat or poultry meat exposed to ionizing radiation has been conducted under conditions suitable for application in commercial operations using gamma radioisotopes (Thomas and Josephson, 1970;deGroot et al, 1976;Howker et al, 1976; Scientific Article Number A-4848.…”
Section: Introductionmentioning
confidence: 98%